INTERCULTURALITY AND ITS LINGUISTIC CONSIDERATION: THREE PARADIGMS - Csaba Földes (Езиков свят)
This article is based on the understanding that language is highly complex and has a cognitive, cultural, and formal component. Within this framework, the focus is on the network of relationships regulated by multiple perspectives between culture and language (both as system and as usage), particularly considering the multifaceted term “interculturality”. First, in order to establish a common ground, I provide an overview of the different concepts of the interaction between language and culture in the linguistic research discourse. Furthermore, an overview of the various culture-sensitive linguistic analytical approaches will be developed. In the main body, three recent paradigms, each of different provenance, will be critically presented and compared regarding their content-related concept and their performance potential. These are (a) Russian and post-Soviet “Linguoculturology” (LC), (b) Anglophone “Cultural Linguistics” (CL), and (c) “Intercultural Linguistics” (IL), primarily origininating in German Studies with a particular focus on multilingualism. It becomes apparent that LC investigates the influence of language on culture, whereas CL aims its attention at the influence of culture on language, while in IL, multi-culturality as well as inter- and transculturality are the focal point. The presented paradigms differ significantly with regard to their respective underlying understanding of culture and their disciplinary orientation: LC and CL exhibit a distinctive cognitive orientation, whereas IL is more based on Contrastive Linguistics and Cultural Studies. The conducted analysis gives evidence of the isolated development of all three schools of thought, especially LC and CL, despite their almost identical research objectives.